Parry–Romberg Syndrome with Uhthoff’s Phenomena: A Spectrum of Autoimmune Disease? - Samuel Asanad (Case Reports in Immunology)
Parry–Romberg syndrome (PRS) is a rare disorder characterized by unilateral facial atrophy. Currently, the pathogenesis of PRS is poorly understood and no definitive treatment is available. This article reports the case of a 51-year-old woman with progressive hemifacial atrophy following herpes zoster infection, who presented with a concomitant chronic history of heat-induced diplopia. Magnetic resonance imaging showed unilateral cerebral white matter, periventricular, and medial longitudinal fasciculus lesions. The patient’s diplopia resolved following treatment with valacyclovir. Infection has been previously considered as potential cause of PRS. However, herpes-induced PRS with ophthalmologic manifestations of Uhthoff’s phenomena has not previously been reported. The present case suggests that PRS may possibly have an autoimmune etiology resembling that of multiple sclerosis.